Adaptability of Mutant Genotypes of Artemisia (Artemisia annua L.) as Result Of Gamma Irradiation in Three Locations with Different Altitude - Syukur, Muhamad; Lestari, Endang Gati; Purnamaningsih, Ragapadmi; Yunita, Rosa; Aisyah, Syarifah Iis; Firdaus, Rohim (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2011)
The objective of this study was to identify the adaptability of twelve artemisia mutant genotypes, which were planted in three locations with different altitude, as a result of gamma irradiation. Randomized Complete Block Design (RCBD) was applied in this research with three replications as blocks. The genotypes 1B, 1C, 1D, 2, 3, 4, 5A, 6B, 7A, 8, 14, 15 and two control genotypes as parent genotype from seed and from in vitro were used. The genotypes were planted in three different locations such as Mount Putri, Cianjur (1450 m above sea level), Pacet, Cianjur (950 m above sea level) and Cicurug, Sukabumi (540 m above sea level). Based on the method of postdictive and predictive success, the model used was AMMI2 which was able to explain up to 100% of interaction-influenced variation. The genotypes which were found stabile and adaptive in these three locations were 1B, 1C, 1D, 6B and 15. Genotypes 3 and 7A were adaptive specifically in Pacet area, 5A was adaptive for Gunung Putri while genotype 4 was for Cicurug only.Keywords: AMMI, Artemisia annua, mutant genotype, adaptability